2014
DOI: 10.1186/1742-2094-11-93
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of inflammatory cytokines in impairing biochemical processes for learning and memory after surgery in rats

Abstract: BackgroundPatients with postoperative cognitive dysfunction have poor outcomes. Neuroinflammation may be the underlying pathophysiology for this dysfunction. We determined whether proinflammatory cytokines affect the trafficking of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors to the plasma membrane, a fundamental biochemical process for learning and memory.MethodsFour-month-old male Fischer 344 rats were subjected to right carotid exposure under isoflurane anesthesia. Some rats received intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…Anesthetic choice for surgery is easy to achieve if it is a modifiable factor for POCD. Many animal studies have found that exposure to volatile anesthetics including isoflurane for a long time can induce brain cell injury and cognitive impairment (Xie et al 2008;Fidalgo et al 2012;Tan et al 2014). They can also induce mild neuroinflammation ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Anesthetic choice for surgery is easy to achieve if it is a modifiable factor for POCD. Many animal studies have found that exposure to volatile anesthetics including isoflurane for a long time can induce brain cell injury and cognitive impairment (Xie et al 2008;Fidalgo et al 2012;Tan et al 2014). They can also induce mild neuroinflammation ).…”
Section: Discussionmentioning
confidence: 95%
“…Based on those data, it was estimated by analysis of variance that each group needed 10 rats to detect a minimum difference in means of 30 % among the three groups with an expected standard deviation of residuals at 20 % and a desired power of 0.8 at an α level of 0.05. Based on the proinflammatory cytokine data published in our previous studies (Zhang et al 2014a, b;Tan et al 2014) and estmated by analysis of variance, 4 rats in each were needed to detect a minimum difference in means of 60 % among the three groups with an expected standard deviation of residuals at 20 % and a desired power of 0.8 at an α level of 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Centrally released cytokines, including TNF-α, IL-1β, and IL-6, have also been implicated in processes of synaptic formation and scaling, long-term potentiation (LTP), and neurogenesis (61). Recent studies have highlighted some of the possible mechanisms whereby surgery and the ensuing inflammatory response contribute to cognitive decline, including changes in synaptic plasticity (62,63), α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) trafficking (64), and N-methyl-D -aspartate receptor (NMDA) subtype 2B (NR2B) expression (65).…”
Section: Neuroinflammation and Cns Functionmentioning
confidence: 99%
“…Accumulating evidences have demonstrated that neuroinflammation plays a substantial role in the pathogenesis of POCD (8)(9)(10)(11)(12)(13)(14)(15). Systemic pro-inflammatory cytokines in response to aseptic surgical trauma disrupt the blood-brain barrier integrity, facilitate the migration of macrophages into the brain parenchyma and induce subsequent neuroinflammation (16).…”
mentioning
confidence: 99%
“…Animal studies have shown that the development of POCD is associated with significantly enhanced expression of pro-inflammatory cytokines, including TNF-α, IL-1, IL-6, and high-mobility group box 1 protein (HMGB1) (8)(9)(10)(11)(12)(13)(14)(15). Several lines of evidence have demonstrated that primed microglia are the main cellular source for this amplified neuroinflammatory response in the development of POCD (5, 21).…”
mentioning
confidence: 99%